Comparison of two technics of cardiopulmonary bypass (conventional and mini CPB) in the trans-and postoperative periods of cardiac surgery - Pereira,Sergio Nunes (2015)
Abstract Objective: This study aimed to compare the effects of two different perfusion techniques: conventional cardiopulmonary bypass and miniature cardiopulmonary bypass in patients undergoing cardiac surgery at the University Hospital of Santa Maria - RS. Methods: We perform a retrospective, cross-sectional study, based on data collected from the patients operated between 2010 and 2013. We analyzed the records of 242 patients divided into two groups: Group I: 149 patients undergoing cardiopulmonary bypass and Group II - 93 patients undergoing the miniature cardiopulmonary bypass. Results: The clinical profile of patients in the preoperative period was similar in the cardiopulmonary bypass and miniature cardiopulmonary bypass groups without significant differences, except in age, which was greater in the miniature cardiopulmonary bypass group. The perioperative data were significant of blood collected for autotransfusion, which were higher in the group with miniature cardiopulmonary bypass than the cardiopulmonary bypass and in transfusion of packed red blood cells, which was higher in cardiopulmonary bypass than in miniature cardiopulmonary bypass. In the immediate, first and second postoperative period the values of hematocrit and hemoglobin were higher and significant in miniature cardiopulmonary bypass than in the cardiopulmonary bypass, although the bleeding in the first and second postoperative days was higher and significant in miniature cardiopulmonary bypass than in the cardiopulmonary bypass. Conclusion: The present results suggest that the miniature cardiopulmonary bypass was beneficial in reducing the red blood cell transfusion during surgery and showed slight but significant increase in hematocrit and hemoglobin in the postoperative period.